THE INFLUENCE OF AGGREGATE MAXIMUM DIAMETER AND VARIABLE OF SPECIMEN SIZE ON CONCRETE COMPRESSIVE TEST - Aman Subakti; Tavio Tavio (Institut Teknologi Sepuluh Nopember (ITS), 2011)
Quality control problems of great importance in supporting the successful development of the project, due to carry out quality control results will be obtained in accordance with the terms specified techniques. Form of the test object in the implementation of quality control may affect the accuracy of the results, especially on standardized test specimens are not generated from the test piece drill cores. There are several sizes of test objects used in accordance with regulations such as PBI 1971dan British Standard (BS) using the test specimen size 15x15x15 cm 3, 20x20x20 cm3. ACI 318, ASTM C42/C42M 2003, using a cylindrical test specimen dimensions 15x30 cm. There is a discourse of the specimen size 10x20 cm due to the size of the specimen is sufficient in number when using a laboratory mixer other than that estimated difference with the test results are not significant 15x30. Test specimen 15x15x15 and 20x20x20 cm cube estimated results are less rigorous than the cylinder, because the cube distribution voltage is not equal than the cylinders which form a circle so that distribution is the same if the specimen is pressed. Taking the test object with a core drill is sometimes produced beyond the standard test specimen is less than 15 cm, 10 cm even for the special conditions of the drill core of 5 cm. Reasons mentioned above the authors conducted research on